2017
DOI: 10.1103/physrevd.96.094021
|View full text |Cite|
|
Sign up to set email alerts
|

Strong decays of exotic and nonexotic heavy baryons in the chiral quark-soliton model

Abstract: In the large N c limit both heavy and light baryons are described by the universal mean field, which allows us to relate the properties of heavy baryons to light ones. With the only input from the decays of light octet baryons (due to the universality of the chiral mean field), excellent description of strong decays of both charm and bottom sextets is obtained. The parameter-free prediction for the widths of exotic antidecapentaplet (15) baryons is also made. The exotic heavy baryons should be anomalously narr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 58 publications
2
35
0
Order By: Relevance
“…With the coupling constants obtained by composition condition, the decays through hadronic loops are calculated in a phenomenological effective Lagrangian approach.The total decay widths can be well reproduced with the assumption that the Ω * c (3119) or Ω * c (3050) as S -wave ΞD bound state with J p = 1/2 − , which decay channels are S −wave Ξ c K, Ξ It is interesting to compare our results with those in Refs. [10,[14][15][16][17][18][19]. According to Ref.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…With the coupling constants obtained by composition condition, the decays through hadronic loops are calculated in a phenomenological effective Lagrangian approach.The total decay widths can be well reproduced with the assumption that the Ω * c (3119) or Ω * c (3050) as S -wave ΞD bound state with J p = 1/2 − , which decay channels are S −wave Ξ c K, Ξ It is interesting to compare our results with those in Refs. [10,[14][15][16][17][18][19]. According to Ref.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…[13], it was found that four sscqq states with J P = 1/2 − or J P = 3/2 − have masses close to the newly observed Ω * c states. In the chiral quark-soliton model, pentaquark-like structures were suggested for the Ω * c (3050) and Ω * c (3119) [14,15]. Since the Ξ ′ cK and ΞD thresholds fall in the mass region of the LHCb observed Ω * c states, hadronic molecule interpretations can not be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [3,4] we have proposed to interpret these two narrow states as exotic pentaquarks using as a guidance the Chiral Quark Soliton Model [5] (χ QSMfor review see Refs. [6,7]).…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [3,4,17] a phenomenological analysis of heavy baryon properties has been performed in the framework of the χ QSM (see also [18][19][20]). It turned out that all decay widths have been very well reproduced [4], also the two narrowest ones of the putative pentaquarks.…”
Section: Introductionmentioning
confidence: 99%
“…These excited Ω c and Ω b states are good candidates of Pwave charmed and bottom baryons. To understand them, many phenomenological methods and models have been applied, such as various quark models [13][14][15][16][17][18][19][20][21][22][23][24][25][26], the chiral perturbation theory [27,28], the molecular model [29][30][31][32][33][34][35][36], Lattice QCD [37,38], and QCD sum rules [39][40][41][42][43][44][45][46][47][48][49][50][51], etc. We refer to reviews [7,[52][53][54] and references therein for their recent progress.…”
Section: Introductionmentioning
confidence: 99%